Resveratrol and Resveratrol-Aspirin Hybrid Compounds as Potent Intestinal Anti-Inflammatory and Anti-Tumor Drugs - Mohamed Salla; Vrajesh Pandya; Khushwant S. Bhullar; Evan Kerek; Yoke Fuan Wong; Robyn Losch; Joe Ou; Fahad S. Aldawsari; Carlos Velazquez-Martinez; Aducio Thiesen; Jason R. B. Dyck; Basil P. Hubbard; et al. (Molecules, 2020)
Resveratrol (3,4,5-Trihydroxy-trans-stilbene) is a naturally occurring polyphenol that exhibits beneficial pleiotropic health effects. It is one of the most promising natural molecules in the prevention and treatment of chronic diseases and autoimmune disorders. One of the key limitations in the clinical use of resveratrol is its extensive metabolic processing to its glucuronides and sulfates. It has been estimated that around 75% of this polyphenol is excreted via feces and urine. To possibly alleviate the extensive metabolic processing and improve bioavailability, we have added segments of acetylsalicylic acid to resveratrol in an attempt to maintain the functional properties of both. We initially characterized resveratrol-aspirin derivatives as products that can inhibit cytochrome P450 Family 1 Subfamily A Member 1 (CYP1A1) activity, DNA methyltransferase (DNMT) activity, and cyclooxygenase (COX) activity. In this study, we provide a detailed analysis of how resveratrol and its aspirin derivatives can inhibit nuclear factor kappa B (NFκB) activation, cytokine production, the growth rate of cancer cells, and in vivo alleviate intestinal inflammation and tumor growth. We identified resveratrol derivatives C3 and C11 as closely preserving resveratrol bioactivities of growth inhibition of cancer cells, inhibition of NFκB activation, activation of sirtuin, and 5’ adenosine monophosphate-activated protein kinase (AMPK) activity. We speculate that the aspirin derivatives of resveratrol would be more metabolically stable, resulting in increased efficacy for treating immune disorders and as an anti-cancer agent.